2022
DOI: 10.3390/ani12131681
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Muscle and Adipose Tissue in Pigs Fed with Addition of Natural Sorbents

Abstract: The fatty acid composition of meat and fat was studied in Choice Genetics line pigs fed a diet with three natural sorbents. Control (C1 and C2), biochar (D, 0.5%), bentonite–montmorillonite (A, 1.5%) and zeolite–clinoptilolite (B, 1.5%) diets were used in two trials. The samples of back fat, kidney fat and Longissimus lumborum (MLL) and Semimembranosus (MSM) muscle were examined. All sorbents (D, A and B) had no effect on fatty acid composition in MLL, whereas in MSM turned out to be very limited and inconsist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These additives are safe in the amount of 0.2-1% of a commercial diet for broilers or pigs and have no negative effect on production, even improving poultry productivity [11]. Previous research has shown their effects on the fatty acid profile of kidney fat [12]. Appropriately chosen, small amounts of the sorbents used are an important factor in the safety of their application and potential negative effects on tissues and cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…These additives are safe in the amount of 0.2-1% of a commercial diet for broilers or pigs and have no negative effect on production, even improving poultry productivity [11]. Previous research has shown their effects on the fatty acid profile of kidney fat [12]. Appropriately chosen, small amounts of the sorbents used are an important factor in the safety of their application and potential negative effects on tissues and cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the influence of the probiotic Sporo-Lex on the concentration of bacteria of the Escherichia coli group in feces, it was established that in the animals of the experimental group, on the 25th day, a significant decrease in the concentration of coli group bacteria was observed to (3.2±0.7)×10 5 , while in the animals of the control group group their concentration was (9.8±0.3)×10 5 .…”
mentioning
confidence: 99%